Memaknai Pengasingan Orang Melayu-Indonesia di Ceylon, Sri Lanka - Oman Fathurahman (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2022)
Ronit Ricci. 2019. Banishment and Belonging: Exile and Diaspora in Sarandib, Lanka, and Ceylon. Cambridge: Cambridge University Press.This essay reviews a book that explores Sri Lanka, one of the historical destinations of colonial exile, with a focus on the literary traditions of the Malay people, particularly Muslims. By using manuscripts written by exiles as the primary source, this work emphasizes contextual studies on dimensions of humanity and culture (manuscript cultures) to explain the experiences of exiles in the formation of the diaspora tradition of the Malay Muslim community. These sources prove that despite being forced to leave their homeland, the exiles were able to construct a religious paradigm that granted them the ability to deal with these political consequences while somehow countering the colonialists’ narratives. Therefore, this book suggests that due to the significant influence of Malay, particularly Islam, this region cannot be disregarded on the map of Southeast Asian Islamic studies. Additionally, this work implies that the concept of “Malay” is not only limited to a region of Southeast Asia today but also includes other regions with a history and culture of producing Malay manuscripts, such as Sri Lanka.